Probiotics and Synbiotics Addition to Bama Mini-Pigs' Diet Improve Carcass Traits and Meat Quality by Altering Plasma Metabolites and Related Gene Expression of Offspring - Zhu, Qian; Song, Mingtong; Azad, Md. Abul Kalam; Ma, Cui; Yin, Yulong; Kong, Xiangfeng (Frontiers in Veterinary Science, 2022)
This study evaluated the effects of maternal probiotics and synbiotics addition on a range of traits and parameters in offspring. A total of 64 Bama mini-pigs were randomly divided into control, antibiotic, probiotics, or synbiotics groups and fed experimental diets during pregnancy and lactation. After weaning, two piglets per litter and eight piglets per group were selected and fed a basal diet. Eight pigs per group were selected for analysis at 65, 95, and 125 days of age. The results showed that probiotics addition increased the average daily feed intake of pigs during the 6695-day-old period and backfat thickness at 65 and 125 days of age, whereas synbiotics addition increased backfat thickness and decreased muscle percentage and loin-eye area at 125 days of age. The addition of probiotics and synbiotics increased cooking yield, pH45min, and meat color, while decreasing drip loss and shear force at different stages; however, maternal antibiotic addition increased shear force in 125-day-old pigs. Dietary probiotics and synbiotics in sows’ diets increased several amino acids in the plasma and longissimus thoracis (LT) muscle, including total amino acid, His, Met, Asp, Arg, and Leu, and decreased Gly, Pro, Ileu, α-AAA, α-ABA, β-Ala, and γ-ABA at different stages. In the LT muscle fatty acid (FA) analysis, saturated FA (including C16:0, C17:0, and C20:0) and C18:1n9t content were lower, and C18:2n6c, C16:1, C20:1, and unsaturated fatty acid content were higher in the probiotics group. C10:0, C12:0, and C14:0 content were higher in 65-day-old piglets, and C20:1 and C18:1n9t content were lower in the synbiotics group. Plasma biochemical analysis revealed that the addition of maternal probiotics and synbiotics decreased plasma ammonia, urea nitrogen, and glucose levels, while synbiotics addition increased plasma alanine aminotransferase, high density lipoprotein-cholesterol, and total cholesterol levels at different stages; moreover, maternal probiotics and synbiotics regulated muscle fiber type, myogenic regulation, and lipid metabolism-related gene expression in offspring. In conclusion, maternal probiotic and synbiotics addition as a nutritional intervention strategy improved feed intake and meat quality by altering the metabolism of offspring and gene expression related to meat quality.